The role of infrastructure in national economic development in Malaysia - Azam, Muhammad; Abu Bakar, Nor'Aznin (2018)
This paper investigates the impact of infrastructure development along with some other predictors' namely inward Foreign Direct Investment (FDI) and human capital on economic growth in Malaysia over the period of 1975-2015. The ordinary least method is employed based on the nature of the data. The least squares results reveal that infrastructure has significantly positive impact on economic growth of Malaysia during the period under the study. The other variables- incoming FDI and human capital are positively related to economic growth. Empirical findings of the study suggest that the government of Malaysia needs to focus more on the development of infrastructure in the country. Improved infrastructure will boost economic growth and consequently will largely improve welfare of the society.